Mayo Clinic wellness solutions for high blood pressure [videorecording (DVD)] (Mayo Clinic, 2007)
Physicians from the esteemed Mayo Clinic of Rochester, Minnesota provide male and female adult views insights on the most effective methods for reducing hypertension. Sections: Integrative Medicine, Gentle Yoga, and Daily Nutrition.